Tryptophan Metabolism by Gut Microbiome and Gut-Brain-Axis: An in silico Analysis - Kaur, Harrisham; Bose, Chandrani; Mande, Sharmila S. (Frontiers in Neuroscience, 2019)
The link between gut microbiome and brain is being slowly acknowledged due to the speculated role of resident gut microbial community in altering the functions of gut-brain axis (GBA). Recently, a number of microbial metabolites (referred to as neuro-active metabolites) produced through tryptophan metabolism have been suggested to influence the GBA. In view of this, the current study focuses on microbial tryptophan metabolism pathways which produce neuro-active metabolites. An in silico analysis was performed on bacterial genomes as well as publicly available gut microbiome data. The results provide a comprehensive catalogue of the analyzed pathways across bacteria. The analysis indicates an enrichment of tryptophan metabolism pathways in five gut-associated phyla, namely Actinobacteria, Firmicutes, Bacteroidetes,Proteobacteria and Fusobacteria. Further, five genera namely, Clostridium, Burkholderia, Streptomyces, Pseudomonas, and Bacillus have been predicted to be enriched in terms of number of the analyzed tryptophan metabolism pathways, suggesting a higher potential of these bacterial groups to metabolize tryptophan in gut. Analysis of available microbiome data corresponding to gut samples from patients of neurological diseases and healthy individuals suggests probable association of different sets of tryptophan metabolizing bacterial pathways with the etiology of different diseases. The insights obtained from the present study are expected to provide directions towards designing of microbiome based diagnostic and therapeutic approaches for neurological diseases/ disorders.